CITREX 2023 - Congratulations to all winners from CMS - Nadirah, Mohd Nasir (2023)
Centre for Mathematical Sciences would like to congratulate the winners of the 13th Creation, Innovation, Technology & Research Exposition (CITREX 2023) which has been held on 13 – 14 March 2023 at Sport Complex, UMP Gambang Campus.